Punctal function in lacrimal drainage: the 'pipette sign' and functional ectropion. (5th May 2015) - Beigi, Bijan; Gupta, Deepak; Luo, Yvonne H‐L; Saldana, Manuel; Georgalas, Ilias; Kalantzis, George; El‐Hindy, Nabil
<x xml:space="preserve">Abstract</x> Background The aim was to assess the movements of the inferior punctum during blinking and discuss pertinent clinical applications. Methods This is a prospective, non‐comparative observational case‐series examining the function of inferior punctum during blinking using video recordings of the blinking action at the slitlamp with slow‐motion analysis and comparison. Results In all 56 eyes of 28 patents, supero‐medial movement of the lower punctum toward the medial canthus, together with a medially directed protrusion of the inferior punctum was noted. It was also noted that the punctum blanched during this projectile movement compared to the rest of the lid margin. Simultaneous posterior rotation of the punctum was also observed in 48 eyes (85.7 per cent; 23 right eyes and 25 left eyes), resulting in apposition of the punctum to the lacus lacrimalis. In eight eyes (14.3 per cent; five right eyes and three left) from six patients, co‐existence of medial punctal ectropion led to failure of internal rotation of the punctum during blinking, even though punctal 'pipette formation' was preserved. These six patients all suffered from epiphora in the affected eyes. The presence of 'pipette' formation was calculated to have a sensitivity of 80 per cent and specificity of 100 per cent for punctal ectropion in our series. A two‐tailed Fisher exact test showed that based on our 56 eyes, these results were statistically significant (p < 0.0001). Conclusions The inferior punctum plays an active and important role in the drainage of tears by the mechanism of supero‐medial movement and medially directed protrusion ('pipetting action'), failure of which contributes to epiphora. This is a highly specific sign and should be sought in the evaluation of epiphora, even in the absence of frank ectropion. In punctual stenosis where location of the punctal orifice is proving difficult, inducing the pipette sign will help in its identification.